Podrugi - Arnstam, Leo (Soviet Union : LenFilm, 1935)
An early Soviet film about the childhood and youth of the three girlefirends from the proletarian suburbs of Petrograd and their participation in the defence of the city against the foreign intervention in 1919. The cast incudes Nikolai Cherkasov and Yanina Zhejmo among others. The musical script was written by Dmitri Shostakovich.
Duration: 01:35:00
Keywords: Fiction films